2019
DOI: 10.1111/os.12469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spinopelvic Alignment on Pelvic Tilt after Total Hip Arthroplasty

Abstract: Objective To evaluate the impact of spinopelvic parameters and hip contracture on change in the pelvic tilt (PT) after Total hip arthroplasty (THA). Methods One hundred patients (15 male and 85 female) who underwent THA were included in this prospective study. Radiographic data were obtained preoperatively and 1 year after THA. Radiographic parameters included sagittal anterior pelvic plane (APP), sagittal vertical axis (SVA), sacral slope (SS), pelvic inclination (PI), and lumbar lordosis angle (LL). The APP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(47 reference statements)
0
10
2
Order By: Relevance
“…The component positioning and dynamic function are being extensively studied as significant factors in THA stability and survival [ 9 , 19 , 23 , 24 ]. The current literature focuses on understanding individual lumbopelvic sagittal kinematics and the relationship with functional cup alignment during daily life activities [ 13 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The component positioning and dynamic function are being extensively studied as significant factors in THA stability and survival [ 9 , 19 , 23 , 24 ]. The current literature focuses on understanding individual lumbopelvic sagittal kinematics and the relationship with functional cup alignment during daily life activities [ 13 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 suggested that pelvic posterior tilt occurred a little up to 7 years postoperatively, and Kanto et al . 31 and Blondel et al . 19 reported no significant changes happened in PST in the first year after THA.…”
Section: Discussionmentioning
confidence: 92%
“…For the patients with simple hip OA, Shareghi et al 17 . suggested that pelvic posterior tilt occurred a little up to 7 years postoperatively, and Kanto et al 31 . and Blondel et al 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ROC analysis showed that ATMS ≤ 4.3 kPa and SS ≤ 31.9° were associated with spinal sagittal imbalance and may be useful predictors of progressive spinal sagittal imbalance before THA. Although many reports evaluated spinopelvic alignment immediately after THA [ 10 , 11 , 12 , 22 , 23 , 24 , 25 , 26 ], to our knowledge, no studies have reported the risk of spinal sagittal imbalance in the long-term course after THA. Spinal sagittal imbalance after THA may lead to a demand for corrective surgery.…”
Section: Discussionmentioning
confidence: 99%